The influence of subjective norms on the use of heat pumps in achieving sustainable development - Nikolić-Ristić, Dragana (Anali Ekonomskog fakulteta u Subotici, 2023)
Sustainable development, use of renewable energy sources and energy efficiency have been the focus of interest of the scientific and professional public in recent decades. The aim of the research is to investigate the influence of subjective norms on the use of heat pumps within the framework of behavior in the function of energy efficiency. In addition, the profile of consumers is investigated in the context of their sociodemographic characteristics. Marketing research was conducted on a convenience sample of 208 respondents on the territory of the Republic of Serbia, in August 2019. The measurement of subjective norms according to the heat pump was performed on the basis of a Likert scale, while the analysis of the sociodemographic characteristics of the respondents was performed using the SPSS program package. Based on the results of the research, it was concluded that the influence of subjective norms on the introduction of the use of heat pumps is closest to the score 3, which is neutral on a five-point Likert scale, as well as that subjective norms can be statistically significantly explained by income and the number of children under the age of 18 as sociodemographic characteristics of the respondent.